PERAN EKONOMI SYARIAH DALAM MENINGKATKAN KETAHANAN PANGAN DI ERA PERUBAHAN IKLIM - Candra, Jeki; K, Kamilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
Climate change poses a serious challenge to global food security, especially in developing countries that depend on the agricultural sector. This article aims to analyze the role of Islamic economics in improving food security in the era of climate change by using the literature study method. The results show that Islamic economics, especially Islamic financial instruments, has a significant contribution in supporting a resilient food system. Islamic economic instruments, such as zakat, waqf, and sharia-based financing, can be utilized to empower farmers, improve access to capital, and fund sustainable agricultural projects. This article concludes that the integration between Islamic economic principles and food security strategies offers a holistic solution to address the impacts of climate change. The findings provide recommendations for policy makers, Islamic financial institutions and local communities in strengthening an equitable and sustainable food system.